Optimizing Nepal’s Natural Resources and Mineral Potentialities for Sustainable National Security - Budhathoki, Santosh (Unity Journal, 2025)
The abundant natural resources of Nepal, such as its minerals, forests, water resources, and potential for renewable energy, provide impetus for augmenting national security as well as economic growth that is sustainable. On the contrary, factors such as poor infrastructure, Policy inconsistencies and inappropriate enforcement of the laws have blocked full realization. In this regard, this appraisal provides a detailed resource management critique of Nepal and puts forward some measures in which resource utilization practices can be used for the benefit of national security. In analyzing the current situation, policy literature reviews, government publications, best practices, and scientifi c articles were used; the study shows the policy and management systems regarding community enclosing different segments of society to resources perform poorly. The systematic review on the basis of exclusive and inclusive criteria reinforces the connection between security and economic development by analyzing Nepal’s resource management. It highlights obstacles like poor infrastructure, policy gaps, and weak enforcement while proposing a Strategic Resource Management Plan. The Nepali Army, and international collaboration, the study suggests that better resource utilization can enhance national security, foster socio-economic balance and combat climate change. Some of these are enhancing the existing laws and policies, employing the Nepal army to protect natural resources, and collaborating with foreign countries to promote technological development and enhancement of human competencies. Such measures will allow Nepal to fully harness resources and enhance economic self-sufficiency, and maintain environmental and socio-economic balance. Besides improving national security, this integrated perspective would also facilitate social solidarity and help Nepal combat climate change, making it a model for sustainable development within the region.